Sistema urbano de drenaje sustentable SUDS para la lotización Pájaro Azul ubicado en km. 10.5 vía a Data del cantón Playas Villamil - Castro Torres, Nelson Leonel (2022)
The research work "Sustainable Urban Drainage System for the Lotización Pájaro Azul Km. 10.5 via Data" is based on the literature analyzed about the shortcomings of the traditional rainwater collection system and the need to implement a new system that is sustainable, environmentally friendly and proves to be a solution for flooding events, in this case in the Lotización Pájaro Azul. Thus, the use of sustainable urban drainage systems (SUDS) was taken into account. To meet this objective, the design of the two systems was carried out, both the traditional rainwater collection system and the design of the sustainable urban drainage system, the SUDS system chosen was the French drain.........